Mechanochemical and Microwave Multistep Organic Reactions - Margetic, Davor (Current Green Chemistry, 2024)
The development of more sustainable chemical reactions and processes has been the focus of recent research activities. Advances in the field of organic synthesis have led to the emergence of new methodologies and techniques involving non-conventional energy sources. These include the applications of mechanical energy (mechanochemistry) and microwave radiation (MW) methods. This article reviews the advances in multistep organic synthesis of biologically relevant organic molecules using mechanochemistry and microwave techniques. Among them, various heterocyclic molecules (with nitrogen, oxygen, and sulphur atoms), amides, and peptides have been synthesized by multistep mechanochemical or MW reactions. Performing multiple synthetic steps using more sustainable methods shows cumulative advantages over multistep processes under conventional conditions in terms of reduced solvent use, shorter reaction times, better turnovers, and reaction yields. Simplification of protocols by carrying out two or more reaction steps in the same reaction vessel is another advantage of multistep syntheses.
Keywords: heterocyclic chemistry